Advanced producer services in Germany: a relational perspective on spatial core–periphery structures, 2009–19. Issue 1 (31st December 2023) - Zöllner, Silke; Heidinger, Mathias; Sager, Sebastian; Lüthi, Stefan; Thierstein, Alain
ABSTRACT: This paper challenges the traditional perspective of a territorial core–periphery pattern as an organizing principle of space by introducing a relational perspective through an empirical approach. We study spatial processes of knowledge creation among advanced producer services in Germany between 2009 and 2019. We use a unique longitudinal dataset to analyse if German regions have become more integrated into the intra-firm location networks nationally and globally, and how this translates into the processes of centralization and peripheralization. The current conceptualization of core–periphery in Germany is too static and does not reflect the economic development of the regions. We find that there is no trend of urban areas becoming more integrated and peripheral areas less integrated into these networks. Instead, our research finds a discrepancy between the federal territorial classification and the functional orientation of German regions. Regions classified as peripheral have not generally decreased in connectivity to other regions. In contrast, some have increased their connectivity and have become more central in relational terms. Overall, we identified peripheralization and centralization as a relational process with dynamic, overlapping and trans-scalar networks.